2001
DOI: 10.1155/2001/271702
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Pain: A Mandate for Change

Abstract: There have been tremendous research advances in the past 15 years in knowledge about children's pain, and strategies for recognizing and managing that pain. However, the clinical care of children in pain remains a challenge. Children's pain continues to be frequently unrecognized, dismissed or ineffectively managed. A loud call for change is being voiced by physicians, nurses, children and their families. A review of the literature was conducted to document this issue. Starting with a Medline search of the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Despite the tremendous advances in researches in children's pain and pain management in past decades, the clinical care of children in pain remains a challenge 1 . Many studies revealed that children in different cultures still suffered from moderate or severe postoperative pain, 2–5 which indicates a need for more effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the tremendous advances in researches in children's pain and pain management in past decades, the clinical care of children in pain remains a challenge 1 . Many studies revealed that children in different cultures still suffered from moderate or severe postoperative pain, 2–5 which indicates a need for more effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…©2003 Pulsus Group Inc. All rights reserved ORIGINAL ARTICLE D espite the publication of the seminal gate control theory of pain (2) in 1965 and the escalation in pain research and knowledge since that time, the management of many people with pain by health professionals remains inadequate. Numerous surveys have found not only the continued occurrence of inadequate pain management for children, elderly persons, and people with cancer or postoperative pain (3,4), but also inadequate knowledge of pain management by various health professional groups such as nursing (5,6), occupational therapy (7-10), physiotherapy (11), pharmacy (12) and medicine (6,13,14).…”
mentioning
confidence: 99%
“…However paediatric health care professionals have the moral obligation to sufficiently and adequately manage pain resulting from the procedures they perform. Several recent studies have documented that pain in children is still underappreciated and undertreated (6,27,29).…”
Section: Discussionmentioning
confidence: 99%